THE ROLE OF SCHOOL COMMITTEE TOWARD THE IMPROVEMENT OF EDUCATION QUALITY AT SDI RIDIK HAWE - Jemali, Maksimilianus; Yosefina Kurniawati (Jurnal Pendidikan dan Kebudayaan Missio, 2025)
This study aims to investigate the role of the school committee in improving the quality of education at Inpres Ridik Hawe Elementary School (SD Impres Redek Hawe). The research was conducted in academic year 2023/2024. Qualitative descriptive research method was employed in narrative form by analyzing non-numerical data. Observation, interview, and documentation were utilized to gather the data. The data were then interpreted following Miles and Huberman’s model of qualitative data analysis, involving three concurrent stages: reduction, data display, and conclusion drawing. To ensure the validity of the research findings, triangulation was conducted by comparing the data from different methods. Several crucial/prominent roles in such cases as guiding and advising the implementation of school policies, providing financial and logistic support, controlling transparency and accountabiliy as well as bridging the school to parents and local government. The study found that the school committee has a positive impact on the improvement of quality at SDI Redek Hawe.